2020
DOI: 10.1177/1534734620934578
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Diabetes Foot Care Education on Amputation Rate in the University of Abuja Teaching Hospital, Nigeria

Abstract: Ulceration of the foot is a major problem for people with diabetes. In a developing country like Nigeria, huge challenge is caused by diabetes foot problems. The aim of this study was to determine the impact of diabetic foot care education of patients and health care staff on the outcome of diabetic foot complications in our hospital. This was a pre and post design carried out from April 2013 to March 2014 on 155 diabetes patients. Patient education was carried out by diabetes nurses and doctors, at diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…The burden of DFU is high both in Africa generally [5], and in Nigeria in particular [6, 7]. A recent update suggests that nearly 2 out of every 10 out‐patients with diabetes in Nigeria have diabetic foot disease [7], and DFU accounts for nearly a third of diabetes‐related hospital admissions [8]. Diabetic foot ulcer is associated with prolonged hospital stay, substantial economic burden and high mortality [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…The burden of DFU is high both in Africa generally [5], and in Nigeria in particular [6, 7]. A recent update suggests that nearly 2 out of every 10 out‐patients with diabetes in Nigeria have diabetic foot disease [7], and DFU accounts for nearly a third of diabetes‐related hospital admissions [8]. Diabetic foot ulcer is associated with prolonged hospital stay, substantial economic burden and high mortality [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…We included 52 articles spanning 39 experimental16 31–68 and 13 non-experimental articles 17 69–80. A Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flow diagram81 was completed to record the number of papers identified, screened and included (figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Focus: In experimental articles, 19 articles focused on diabetic foot care,31 33 34 39 43 45 47–50 55–57 60 61 63 64 67 68 and 20 articles focused on diabetes in general including foot care 16 32 35–38 40–42 44 46 51–54 58 59 62 65 66. In non-experimental articles, eight focused on diabetic foot care,69 71 73 74 76–79 and five articles focused on diabetes in general 17 70 72 75 80…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Nigeria, Anumah et al 10 have demonstrated that education is an inexpensive and effective approach towards prevention of lower-limb amputations. Colak et al 11 have compared collagen granule dressings with conventional dressings in patients with DFUs, showing the benefits of the former.…”
Section: Editorialmentioning
confidence: 99%